Risk of atopic dermatitis in periodontitis patients with and without dental scaling: A retrospective cohort study - Ming-Che Chiang; Chuen-Chau Chang; Chia-Yen Lee; Chun-Chieh Yeh; Yu-Chen Huang; Ta-Liang Chen; Chien-Chang Liao (PLoS ONE, 2025)
Background Both atopic dermatitis (AD) and periodontitis are common chronic inflammatory diseases. However, the association between AD and periodontitis remains poorly understood. This study aimed to evaluate the effects of dental scaling (DS) on the risk of AD among patients with periodontitis. Methods In this retrospective cohort study using health insurance data, we identified individuals aged ≥20 years with periodontitis and a matched cohort without a history of periodontitis in Taiwan from 2011 to 2015. Age- and sex-matching was applied to select controls (ratio = 1:1). Both cohorts were followed until the end of 2017 to monitor atopic dermatitis (AD) incidence. Adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) for AD risk associated with periodontitis were estimated using multivariate Cox regression. Among patients with periodontitis, we compared the risk of AD between those who received DS and those who did not. Results During the follow-up period, patients with periodontitis had an increased risk of AD compared with those without periodontitis (HR 2.47, 95% CI 2.25–2.71). The association between periodontitis and increased risk of AD was significant in men (HR 2.68, 95% CI 2.33–3.08), women (HR 2.35, 95% CI 2.07–2.66), and people in every age group. Among patients with periodontitis (n = 38,943), DS was associated with a reduced risk of AD (HR 0.33, 95% CI 0.30–0.37), and there was a dose-response relationship (p < 0.0001). The beneficial effects of DS on the risk of AD were observed across subgroups. The risk of AD was lowest in patients with periodontitis who received DS more than four times compared with those without DS (HR 0.14, 95% CI 0.08–0.25). Conclusions In conclusion, our study revealed a significant association between periodontitis and increased risk of atopic dermatitis in Taiwanese adults. Moreover, regular dental scaling may lower this risk, underscoring the value of integrating oral care into managing systemic inflammation.